Do Augmented Realty Comics Improve Reading Interest for Elementary School Student in Pandemic Era? - Anisah Widi Astuti; Albi Anggito; Ali Mustadi (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to develop comics in increasing students' reading interest for 4th grade elementary school. Interest in reading is important for students in the learning process. This research is a research and development (RD) using the Borg Gall research model. The purpose of this research is to produce appropriate and effective comic media to increase the reading interest of elementary school students. The subjects of this study were 4th grade students of G.S. elementary school. Data collection was done using observation, interviews, questionnaires and scales. The effectiveness of the media was tested with a non-equivalent control group design. The results of the study were tested for prerequisites with a normality test (0.001) and a homogeneity test in the control class (0.044), so that further different tests could be carried out. The feasibility test got d the average final result of material validation was 4.54 (very feasible) and media validation was 4.30 (very feasible). Test results paired sample t-test asymp. value. Sig. (2-tailed) 0.001 0.05 so that H0 is rejected and H1 is rejected (accepted) which means that there is a significant difference in students' reading interest before and after using augmented reality-assisted comics media. Meanwhile, the results of the calculation of the Mann Whitney test obtained asymp results Sig. (2-tailed) of 0.044 is smaller than the probability value of 0.05, so H0 is rejected and H1 is accepted, which means that there is a significant difference in students' reading interest when using AR-assisted comics in the experimental class with students using slide presentation media in the control class. Therefore, it can be concluded that product augmented reality-assisted comics are effective in increasing reading interest in 4th grade elementary school students.